OBSTACLE IN J.R.R TOLKIEN'S NOVEL THE HOBBIT - Pramudia Deska Ananda; Safitri - Hariani (JOURNAL OF LANGUAGE, 2019)
This article is about the protagonist’s obstacles and the solutions for the obstacles in John Ronald Reuel Tolkien’s novel The Hobbit which is published in 1937. The Hobbit is about adventure in searching of dragon guarded gold. The protagonist’s name is Bilbo Baggins. On his journey, he undergoes some obstacles such as being arrested by the trolls, being attacked and arrested by the goblins, falling down to the dark cave, being pursued by the wolves, and fighting with the spider. There are two solutions which are needed in solving the obstacle; ingenuity and physical endurance. This analysis uses the data  taken from the novel applying Descriptive Qualitative Research. One of the dominant concepts of obstacle used in this study is proposed by Brian Kariger and Daniel Fierro (1998) who state that obstacle is something that obstructs or hinders progress. The conclusion from this analysis shows that the protagonist, Bilbo Baggins faces some obstacles and there are two solutions to solve the obstacles.